Penentuan Jumlah Operator Bagian Packing dengan Menggunakan Metode Antrian Guna Mengurangai Waktu Tunggu dan Biaya - Teguh Baroto, Ayudina Puji E (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
The queue in packing division PT. Domusindo Perdana caused of product arriving that will be packed over than service facilities available so that long queuing happened and it makes long waiting time that will be caused to high totally cost.Alocation of operator number in packing division that have lot of queue is in Centre of Panel (1 person), Base Assembly (1 person), Drawer Side, Back, Base (1 person) and strawpack (4 persons) after analysis of queuing. Using searching analysis of optimum working number, will increase operator in Centre Panel Devision (3 person), Base Assembly (3 persons), Drawer Side, Back, Base (4 persons) and strapack (5 person) to make these divisions don't have any queue.The increasing of service facilities in packing division from the initial condition 7 persons I operator and in end condition about 15 operators. Overall cost spent everyday decrease about Rp. 117.471.214, 00 than the initial condition Rp. 245.675.136, 00 and the last condition Rp. 67.193.922 with overall waiting time in packing division decrease about 25.20 minutes than the initial condition about 39.6 minutes to 14.4 minutes ..